2016
DOI: 10.3174/ajnr.a5018
|View full text |Cite
|
Sign up to set email alerts
|

Testing Stenting and Flow Diversion Using a Surgical Elastase-Induced Complex Fusiform Aneurysm Model

Abstract: Challenging fusiform aneurysms can be created in rabbits by using a surgical modification of the elastase method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A few studies on FD stents have demonstrated similar histological findings 4. In a recent animal study, neointimal thickness was found to be more extensive in FDs compared with high-porosity stents 19. As ISS is reported in the different FD stent devices, we believe that ISS is inherent to all FD stents likely due to increased strut density.…”
Section: Discussionmentioning
confidence: 63%
“…A few studies on FD stents have demonstrated similar histological findings 4. In a recent animal study, neointimal thickness was found to be more extensive in FDs compared with high-porosity stents 19. As ISS is reported in the different FD stent devices, we believe that ISS is inherent to all FD stents likely due to increased strut density.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, Fahed et al. 81 created a complex fusiform rabbit aneurysm model that permitted more comprehensive testing for flow diverters (Figure 5, E6; Supplementary Figure E6). Avery et al.…”
Section: Resultsmentioning
confidence: 99%
“…With the emergence of novel endovascular technologies that extended the indications for treatment to a broader range of intracranial aneurysm (IA) morphologies, new preclinical models were needed. More recently fusiform 81 and curved sidewall 82 aneurysm models were designed in rabbits and dogs. Darsaut et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations